Hypnosis and the neuroscience of cognitive and affective control - Jaffer, Usman; Jamieson, Graham (Australian Society of Hypnosis, 2012)
This paper examines hypnosis in relation to the neuroscience cognitive and affective control. It is proposed that hypnotic phenomena are rooted in evolution and thus biologically based. Animal hypnosis is considered to confer important advantages in natural selection which have been preserved and extended in the development of the human brain. Two influential models in the neuroscience of cognitive control are described and evidence for brain structures implementing conflict monitoring and cognitive control is reviewed. The neural basis of affective control is then examined in relation to cognitive control. Dorsal anterior cingulate cortex (dACC) is proposed as a common cognitive and affective monitoring mechanism. Ventrolateral prefrontal cortex (vlPFC) is proposed as monitoring stimulus salience whereas the medial prefrontal cortex (mPFC) was involved in the monitoring of affective conflict. The dorsolateral prefrontal cortex (dlPFC) is implicated in resolution of cognitive conflict and the rostral anterior cingulate cortex (rACC) was implicated in affective conflict resolution. Current theories of hypnosis as a dissociative state are then analysed in relation to these models of cognitive and affective control.